Diversidad isoenzimatica de mangos criollos de Chiapas, Mexico - Galvez Lopez, D.=700 1 Adriano Anaya, M.L.; Villareal Treminio, C.
(En, Es)
ilus., 13 ref.
Keywords: MANGIFERA INDICA; VARIACION GENETICA; ISOENZIMAS; GERMOPLASMA; MEXICO